Liability of Debtors for Default on Credit Agreements In Savings and Loan Cooperatives - Noya, Jelien Bridelia; Tjoanda, Merry; Haliwela, Nancy Silvana; Lenggono, Roy Prabowo (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Cooperatives are one of the people's choices to develop their business by lending business capital, in the implementation of credit in savings and loan cooperatives, there are often problems such as late payments (bad loans) to defaults that cause losses for the cooperative, where savings and loan cooperatives have provided benefits to the community according to the purpose of the cooperative.Purposes of the Research: To analyze and review the Debtor's Responsibility for the Default of Credit Agreement in the Savings and Loan Cooperative.Methods of the Research: The research method used is normative juridical with the approach used in this study is a conceptual approach, to answer existing problems, the author collects legal materials through literature studies and analysis with descriptive analysis methods.Findings of the Research: The results of this study show that the implementation of credit in savings and loan cooperatives that occur in the community has not gone well, because there are often verbal credit agreements that cause problems. If the debtor does not resolve the default can be attributed as a default, and the default can be accounted for in court. So that the credit agreement in the savings cooperative must be in writing so that it can be strong evidence and not be a problem, so that the government is obliged to carry out supervision on cooperatives, especially for collection officers who directly go down to the community.